Lectotypifications in the genera Bulnesia (Zygophyllaceae) - Godoy Bürki, Ana Carolina (2015)
Zygophyllaceae Brown (1814, add literature) is distributed in arid and semiarid regions in the tropics and subtropics of the world, comprising 22 genera and 230–240 species of trees, shrubs, sub shrubs and annual or perennial herbs (Sheahan 2007). The family was first divided by Engler (1931) into seven subfamilies and 8 tribes and 4 subtribes. Nonetheless, recent molecular studies only support the recognition of three subfamilies (see Sheahan & Chase 1996, 2000), Larreoideae being the major representative of the family in South America.